2011
DOI: 10.1103/physrevb.83.014301
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational density of states of silicon nanoparticles

Abstract: The vibrational density of states of silicon nanoparticles in the range from 2.3 to 10.3 nm is studied with the help of molecular-dynamics simulations. From these simulations the vibrational density of states and frequencies of bulklike vibrational modes at high-symmetry points of the Brillouin zone have been derived. The results show an increase of the density of states at low frequencies and a transfer of modes from the high-frequency end of the spectrum to the intermediate range. At the same time the peak o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
(55 reference statements)
3
47
0
Order By: Relevance
“…It was found that, as the Si particles become smaller, the density of vibrational states increases at low frequencies, and modes are transferred from the high-frequency end to the intermediate range and transverse optical modes peak are shifted to higher frequencies. 2 In metallic glasses, vibrational characteristics have also been used for explaining mechanical properties. For example, recent MD simulations of a Cu 64 Zr 36 metallic glass showed that the strongest participation in the modes with lowest vibrational frequency and, hence, weakest spring constants (i.e., soft modes) originate predominantly from meagrely populated polyhedra.…”
mentioning
confidence: 99%
“…It was found that, as the Si particles become smaller, the density of vibrational states increases at low frequencies, and modes are transferred from the high-frequency end to the intermediate range and transverse optical modes peak are shifted to higher frequencies. 2 In metallic glasses, vibrational characteristics have also been used for explaining mechanical properties. For example, recent MD simulations of a Cu 64 Zr 36 metallic glass showed that the strongest participation in the modes with lowest vibrational frequency and, hence, weakest spring constants (i.e., soft modes) originate predominantly from meagrely populated polyhedra.…”
mentioning
confidence: 99%
“…We point out that since our results 2 were published, we have independently confirmed the qualitative change of transport properties in our system near the mode-coupling crossover by analysing the temperature evolution of dynamical finite size effects 4 On the basis of their angle-resolved photoemission studies, the group from Tokyo arrived at the conclusion that the metallic state is twodimensional, anisotropic and disperses strongly in a direction perpendicular to the Au-induced nanowires 5,6 . In contrast, the group from Würzburg performed angle-resolved photoemission and scanning tunnelling microscopy (STM) experiments, and concluded that the metallic state is strictly onedimensional and originates from the Auinduced nanowires 2,7,8 . This controversy regarding the dimensionality and dispersion direction of the metallic state can only be resolved by measuring the spatially resolved local density of states (LDOS).…”
mentioning
confidence: 99%
“…Thus, it is very plausible that atom-atom interaction effects are responsible for the softening of the TO phonon at the X point. Using molecular dynamics calculations it was recently shown by Meyer and Comtesse, that the observed redshift in the VDOS regardless from the symmetry point can be explained by the increasing number of surface atoms [15].…”
Section: Vibrational Propertiesmentioning
confidence: 99%